A data-model perspective on the Brazilian margin surface warming from the Last Glacial Maximum to the Holocene - Santos, Thiago P.; Shimizu, Marilia H.; Nascimento, Rodrigo A.; Venancio, Igor M.; Campos, Marília C.; Portilho‐Ramos, Rodrigo C.; Ballalai, João M.; Lessa, Douglas O.; Crivellari, Stefano; Nagai, Renata H.; Chiessi, Cristiano Mazur; Kuhnert, Henning; et al. (Quaternary science reviews, 2022)
The western South Atlantic along the Brazilian margin is an important region for the Atlantic Meridional Overturning Circulation (AMOC) because surface currents in this area transfer warm and salty waters from the Southern Hemisphere to the North Atlantic. Although the number of sea surface temperature (SST) reconstructions has grown in this region, it has been challenging to explain changes in different and sometimes proximal cores. To understand the SST evolution of the Brazilian margin from the Last Glacial Maximum (LGM) to the late Holocene, we present the first SST stack (BRSST stack) for this region. We compare the BRSST stack with the outputs of the transient climate model simulation TraCE-21ka. The BRSST stack shows an LGM cooling of 1.43 °C (from −1.31 to −1.55 °C, 2σ) relative to the late Holocene, followed by deglacial warming starting at ∼ 18.8 ka. TraCE-21ka simulates this early onset of the last deglaciation. Sensitivity experiments suggest that the input of meltwater from retreating ice sheets in the Northern Hemisphere triggered the post-LGM warming, which was subsequently sustained by increasing atmospheric CO2. Deglacial millennial-scale events of AMOC slowdown produced large-scale warming of the Brazilian margin not clearly distinguished by some previous studies. Analyzing our stack in its segregated components, i.e., the North Brazil Current (NBCSST stack) and Brazil Current (BCSST stack) - we noted in-phase warming at the onset of the last deglaciation, which is not found in TraCE-21ka simulations. We attributed this to underestimating the meltwater influence over the tropical Brazilian margin by the model. BRSST stack also presents episodes of abrupt cooling near periods of fast sea-level rise during the last deglaciation, which may be due to rapid AMOC reinvigoration or freshening of the Southern Ocean. Holocene climate resembles that recorded by other compilations, with no clear Holocene thermal maximum but presenting a cooling trend during the late Holocene possibly related to intensified volcanic activity. Our study indicates that the future human-induced SST change expected for the end of the 21st-century will overcome the background of natural climate variability of the last 22,000 years for the Brazilian margin.
Gesehen am 07.07.2022